From Cook to Community Leader: Women’s Leadership at Highlander Research and Education Center - Colleen McDermott (Adult Education Research Conference, 2008)
The purpose of this study was to uncover the roles of the women of Highlander Research and Education Center and analyze how these women influenced not only the curriculum but also the institutional structure of Highlander. Robnett’s (1997) concept of bridge leader provided the theoretical framework for data analysis.
Keywords: highlander; women; activists; social movements